Do standardization and quantification of histopathological criteria improve the diagnosis of inflammatory bowel disease? - Rosimeri Kuhl Svoboda Baldin; José Ederaldo Queiroz Telles; Renato Araújo Bonardi; Heda Maria Barska dos Santos Amarante; Antônio Baldin Júnior (Sociedade Brasileira de Patologia Clínica, 2014)
Introduction: Inflammatory bowel disease comprises two major categories: Crohn's disease and ulcerative rectocolitis, both with different clinical and histological aspects, causing sometimes significant morbidity. Objectives: Choose and apply standardized and quantified histopathological diagnosis method, and compare the results and quality index with the original diagnosis. Materials and methods: 43 histological colonoscopic biopsies of 37 patients were re-evaluated by standardized system. Results and discussion: The original diagnoses were more inconclusive (23.3%) than those standardized (2.3%). The agreement with gold standard (clinical, colonoscopical, and radiological diagnosis) was higher on standardized diagnoses (95.3%) than in original (74.4%), especially in relation to Crohn's disease, which percentages were 92.3% and 46.1%, respectively. The quality index was calculated in conclusive diagnosis of each method. For ulcerative rectocolitis, both methods showed sensitivity and negative predictive value of 100%; otherwise the original diagnosis demonstrated specificity of 85.7%, positive predictive value of 96.3% and accuracy of 97.0%, and the standardized diagnosis 92.3%, 96.7% and 97.6%, respectively. For Crohn's disease, there is specificity and positive predictive value of 100% in both methods; the original diagnosis showed sensitivity of 85.7%, negative predictive value of 96.3% and accuracy of 97%, while for the standardized diagnoses 92.3%, 96.7%, and 97.6%, respectively. Conclusion: The standardized diagnosis presented a higher percentage of correct and conclusive diagnoses than those presented in the original diagnosis, especially for Crohn's disease, as well as equal or slightly higher values in some quality index.